2016
DOI: 10.18632/oncotarget.12954
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tks adaptor proteins in invadopodia formation, growth and metastasis of melanoma

Abstract: Metastatic cancer cells are characterized by their ability to degrade and invade through extracellular matrix. We previously showed that the Tks adaptor proteins, Tks4 and Tks5, are required for invadopodia formation and/or function in Src-transformed fibroblasts and a number of human cancer cell types. In this study, we investigated the role of Tks adaptor proteins in melanoma cell invasion and metastasis. Knockdown of either Tks4 or Tks5 in both mouse and human melanoma cell lines resulted in a decreased abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 54 publications
7
76
1
1
Order By: Relevance
“…Intriguingly, the Tks5‐KD tumors formed by both subcutaneous and tail vein injection displayed lower blood vessel density and blood vessel diameter when compared to controls, raising the possibility that tumor cell invadopodia may also play roles in tumor angiogenesis . In our breast cancer and melanoma studies, we also observed that cells with reduced Tks5 expression grew less well in matrices of type I collagen in vitro . It is of course possible that the reduced tumor growth observed in vitro and in vivo could be due to loss of invadopodia‐independent functions of Tks5.…”
Section: Podosomes and Invadopodia Are Present In Diverse Cell Typesmentioning
confidence: 70%
See 4 more Smart Citations
“…Intriguingly, the Tks5‐KD tumors formed by both subcutaneous and tail vein injection displayed lower blood vessel density and blood vessel diameter when compared to controls, raising the possibility that tumor cell invadopodia may also play roles in tumor angiogenesis . In our breast cancer and melanoma studies, we also observed that cells with reduced Tks5 expression grew less well in matrices of type I collagen in vitro . It is of course possible that the reduced tumor growth observed in vitro and in vivo could be due to loss of invadopodia‐independent functions of Tks5.…”
Section: Podosomes and Invadopodia Are Present In Diverse Cell Typesmentioning
confidence: 70%
“…)? We have shown in three different model systems (mouse fibrosarcoma, human breast cancer, and mouse and human melanoma) that knockdown of Tks5 reduces the in vivo growth of tumors, in subcutaneous, orthotopic, and metastatic sites . Intriguingly, the Tks5‐KD tumors formed by both subcutaneous and tail vein injection displayed lower blood vessel density and blood vessel diameter when compared to controls, raising the possibility that tumor cell invadopodia may also play roles in tumor angiogenesis .…”
Section: Podosomes and Invadopodia Are Present In Diverse Cell Typesmentioning
confidence: 99%
See 3 more Smart Citations